2000
DOI: 10.1111/j.1469-185x.1999.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant invasions — the role of mutualisms

Abstract: Many introduced plant species rely on mutualisms in their new habitats to overcome barriers to establishment and to become naturalized and, in some cases, invasive. Mutualisms involving animalmediated pollination and seed dispersal, and symbioses between plant roots and microbiota often facilitate invasions. The spread of many alien plants, particularly woody ones, depends on pollinator mutualisms. Most alien plants are well served by generalist pollinators (insects and birds), and pollinator limitation does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
464
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 495 publications
(494 citation statements)
references
References 158 publications
9
464
1
1
Order By: Relevance
“…Darlington ' s (1965) arguments were fi rst articulated by Darwin. In the last chapter of On the Origin of Species (1859) , Darwin wrote that ' As natural selection acts by competition, it adapts the inhabitants of each country only in relation to the degree of perfection of their associates; so that we need feel no surprise at the inhabitants of any one country, although on the current state of the hypothesis seems to be that some researchers would prefer to emphasize the role that community diversity plays, even if weak (see, for example, Stachowicz & Tilman 2005 ), whereas others view the poor ability of diversity in natural systems to predict invasibility as damning evidence against the DIH paradigm (Rejm á nek 1996 ; Williamson 1996 ;Huston 2004 ;Davis 2009 ). Still another perspective is the possibility that high levels of diversity imply not only many potential competitors, but also many potential mutualists (Richardson et al 2000 ). Several studies in marine systems in particular have demonstrated links between diversity and facilitative interactions in invasions (see, for example, Stachowicz & Byrnes 2006 ).…”
Section: Considering Dih More Broadly: Were Elton and Macarthur Wrongmentioning
confidence: 99%
“…Darlington ' s (1965) arguments were fi rst articulated by Darwin. In the last chapter of On the Origin of Species (1859) , Darwin wrote that ' As natural selection acts by competition, it adapts the inhabitants of each country only in relation to the degree of perfection of their associates; so that we need feel no surprise at the inhabitants of any one country, although on the current state of the hypothesis seems to be that some researchers would prefer to emphasize the role that community diversity plays, even if weak (see, for example, Stachowicz & Tilman 2005 ), whereas others view the poor ability of diversity in natural systems to predict invasibility as damning evidence against the DIH paradigm (Rejm á nek 1996 ; Williamson 1996 ;Huston 2004 ;Davis 2009 ). Still another perspective is the possibility that high levels of diversity imply not only many potential competitors, but also many potential mutualists (Richardson et al 2000 ). Several studies in marine systems in particular have demonstrated links between diversity and facilitative interactions in invasions (see, for example, Stachowicz & Byrnes 2006 ).…”
Section: Considering Dih More Broadly: Were Elton and Macarthur Wrongmentioning
confidence: 99%
“…In fact, if plant invasions are facilitated by a diverse array of pollinators, dispersers, fungi and bacteria. So, if disturbance and/or fl uctuations in resource availability create windows of opportunity, we should expect invasibility to be positively correlated with native species richness (Richardson et al 2000a ). capacity for autonomous self -pollination), and therefore requires pollinators to set seeds.…”
Section: The Role Of Mutualists In the Naturalizationinvasion Continuummentioning
confidence: 99%
“…Much evidence has accumulated in the last decade from terrestrial and aquatic ecosystems to show that native species frequently promote (facilitate) the colonization and establishment of introduced species through a variety of mechanisms (Richardson et al 2000a ;Bruno et al 2005 ;Badano et al 2007 ;Milton et al 2007 ;Olyarnik et al 2008 ). Simberloff and von Holle (1999) were the fi rst to incorporate facilitation explicitly in an invasion biology framework; they coined the term ' invasional meltdown ' for the process whereby two or more introduced species facilitate establishment and/or spread of each other (and potentially other species).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This interest is associated with recent sea changes in plant ecology in which the effects of positive interactions (i.e. facilitation and mutualisms) are emphasized in shaping natural and invaded communities (Bruno et al 2003 ;Richardson et al 2000 ). Perhaps successful invasions are due in part to the lack of coevolved interactions with soil biota, thus invaders are interacting with microbial symbionts in ways that are more benefi cial through positive feedbacks (Klironomos 2002 ;Packer & Clay 2000 ;Reinhart et al 2003Reinhart et al , 2005Callaway et al 2004a,b ), increased soil nutrient pools (Liao et al 2008 ;Rodgers et al 2008 ;Rout & Chrzanowski 2009 ), and perhaps the accumulation of more beneficial mutualisms.…”
Section: Microbial Mechanisms Underlying Plant Invasionsmentioning
confidence: 99%